INCREASE OF BARLEY TOLERANCE TO TOXICITY OF METALS AND OSMOTIC STRESS USING CELL SELECTION - O. N. Shupletsova; I. G. Shirokikh (Зерновое хозяйство России)
The reaction of barley in callus cultures has been studied using ions Cd2+, Mn2+, Al3+ and PEG as osmotic. Analyzing amount of doses for crop survival, lethal and sublethal metal concentrates were found:  manganese (350 and 250 mg/l, respectively), cadmium (30 and 10 mg/l), aluminum (42 and 20 mg/l). Optimal schemes have been suggested to select callus lines tolerant to a complex of stresses.  To select a line resistant to complex ion toxicity, it has been recommended to use ions of cadmium (20 mg/l) during a proliferation period and ions of manganese (200 mg/l) during a period of morphogenesis. Ions of aluminum (20-30 mg/l) can be used during both stages of callus tissue development, supporting survival of callus and frequency of plant regeneration. To choose callus with total tolerance to ion toxicity and osmotic stress it’s advisable to apply osmotic (10% of PEG) only during a period of morphogenesis, during a proliferation period it’s possible to use aluminum (20 mg/l) with ions of cadmium (20 mg/l) or ions of manganese (200 mg/l). Using the developed scheme of selection we received 50 plants-regenerators of barley for applying them as starting material in crop selection.